Inside Back Cover: Boron Nitride Nanosheets Improve Sensitivity and Reusability of Surface‐Enhanced Raman Spectroscopy (Angew. Chem. Int. Ed. 29/2016). Issue 29 (20th May 2016) - Cai, Qiran; Mateti, Srikanth; Yang, Wenrong; Jones, Rob; Watanabe, Kenji; Taniguchi, Takashi; Huang, Shaoming; Chen, Ying; Li, Lu Hua
Abstract : Atomically thin boron nitride nanosheets have many desirable properties for surface‐enhanced Raman spectroscopy. In their Communication onpage 8405 ff. Y. Chen, L. H. Li, and co‐workers show that when used to cover plasmonic silver nanoparticles (Ag NPs), atomically thin boron nitride nanosheets can enhance the sensitivity by up to two orders of magnitude. The impermeability and thermal stability of boron nitride nanosheets protects the Ag NPs from oxidation so that the substrates can be regenerated by heating in air and reused.